HEMAT LISTRIK DENGAN LAMPU HEMAT LISTRIK - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2015)
Saving electricity is a theme, which draws full attention throughout the general population, but it is rarely considered in relation to the lighting problem. It appeared in Germany, 10% of all the energy needs of 480,000 GWH used illumination purposes, which is subdivided into 20% for private homes (private house hold) and 80% for industry, trade, public lighting and etc.Based on the results of testing in the field of electricity that has been done, proven Power Saving Lamps (PSL) the original but can produce light five times brighter than incandescent lamps with the same wattage, is also able to save electricity to above 70 percent.When calculated level of efficiency, LHL is more efficient than incandescent bulbs. For example, the power light (bright light) LHL by 14 watt comparable to 75 watt incandescent bulb. Likewise lamp life, for LHL can reach 8,000 hours, whereas incandescent lamps only 1,000 hours.